An essential studies on tribology’s: a short review - Ahmad Shahir, Jamaludin; Norazlianie, Sazali; Nor Hasrul Akhmal, Ngadiman (Akademia Baru Publishing (M) Sdn Bhd, 2020)
Recently, there are a few major malfunctions of machinery and plant have been reported because of their weariness and related reasons, and a few of them causing a great financial loss. It is believed that these continuous failures lead to more serious breakdowns of the machinery and expensive. This is closely related to the tribology, in which tribology is the science and engineering that encompasses how interrelating surfaces behave in comparative motion in natural and artificial systems. It is incorporating the research and use of the values of wear, lubrication also friction.